Dinâmica de institucionalização de práticas sociais: estudo da responsabilidade social no campo das organizações bancárias - Ventura, Elvira Cruvinel Ferreira (2005)
The scope of this theses is to understand the dynamics of the institutionalization of Corporate Social Responsibility (CSR) within the Field of Banking Organizations in Brazil. Using the social analysis model put forward by Boltanski and Chiapello (1999) and reverting to the conceptual basis of the institutional approach and using Bourdieu¿s notion of interest (1996), we arrive at an analytical model that enabled us to assess CSR as part of a movement of displacement of capitalism. The theory we propose here is that with the institutionalization of CSR, actions are justified in terms of the common good, being legitimized by structural confirmations and arrangements and, at the same time, heeding the inherent interests of the Field. The means used for comprehension of the dynamics of the institutionalization of CSR were: (1) the analysis of the construction of the phenomenon of CSR, which enabled us to identify critical factors and events, leaders in Brazil and associated ratification of the institutionalization of this social practice; (2) the description of the Field of Banking Organizations and the identification of the elements of its CSR in History, which are essential steps for understanding the justifications for insertion of the Field in the movement towards CSR; (3) the identification of key players in the institutionalization of the social practice within the Field, as well as the categorization of practical actions considered socially responsible to be found in the organizations researched, analyzing them in terms of justifications and interests; (4) the analysis of the dissemination and sedimentation of structural arrangements linked to CSR in the organizations of the Field, such as specific areas created to deal with CSR, social reports and organizational websites. The field research assessed some 30 organizations and included documentary analysis and interviews. We noted that, from being a marginal and isolated action, over the course of the past decade CSR has become a structured action in banking organizations, while at the same time becoming transformed into a social value, capable of contributing to the legitimacy of the Field. In this respect, research showed that retail banks are those that are inserted in the movement towards CSR, which ratifies the thesis of the phenomenon as displacement of capitalism.